Comparison of drug-eluting balloon with repeat drug-eluting stent for recurrent drug-eluting stent in-stent restenosis. Issue 7 (November 2019) - Wang, Guozhong; Zhao, Quanming; Chen, Qing; Zhang, Xiaoxia; Tian, Lei; Zhang, Xiaojiang
Abstract : Objective: Approximately, 10–20% of patients with drug eluting stent (DES) in-stent restenosis (ISR) will develop recurrent ISR; yet, the optimal management of recurrent DES-ISR is unknown. We sought to compare the outcomes of recurrent DES-ISR treated with drug eluting balloons (DEB) to those with repeated implantation of new-generation DES. Methods: A total of 172 patients with recurrent DES-ISR were enrolled and stratified into two cohorts: the repeated DES implantation (Re-DES) group and the DEB group. The primary endpoint was the 1-year incidence of major adverse cardiovascular events (MACE). Results: Ninety-three patients treated with DEB and 79 patients with Re-DES implantation were analyzed. Both groups had comparable baseline characteristics. Lesser residual stenosis was achieved in the Re-DES group (11.3 ± 3.2% vs. 22.4 ± 4.3%; P = 0.00) than in the DEB group. However, the incidence of MACE and target lesion revascularization (TLR) were less in the DEB group (17.2% vs. 32.9%; P = 0.02 and 15.1% vs. 27.8%; P = 0.04, respectively). For the ≥ 3 metal-layered DES-ISR subgroup, DEB drastically reduced the incidences of MACE and TLR compared with Re-DES (20.0% vs. 57.9%; P = 0.02 and 16.0% vs. 47.4%; P = 0.04, respectively). Survival analysis demonstrated that MACE-free survival was significantly higher in the DEB group compared with the Re-DES group, whether the metal layers were ≥3 or 2. Multivariate analysis revealed that the risk factors of MACE were diabetes mellitus, ≥3 metal-layered DES ISR, and repeat DES deployment. Conclusions: For recurrent DES-ISR, DEB may improve clinical outcomes compared with Re-DES implantation, especially for ≥3 metal-layered DES-ISR.